Victoria. The complete third season [videorecording (DVD)] - Sax, Geoffrey; Thomas, Chloe (Director); Coleman, Jenna, 1986-; Hughes, Tom, 1986-; Lindsay, Nigel, 1969- ([publisher not identified], 2019)
Follows the life of Queen Victoria as she ascends the British throne.